Advancing multimodal and critical discourse studies : interdisciplinary research inspired by Theo van Leeuwen's social semiotics - Zhao, Sumin; Djonov, Emilia, 1975-; Björkvall, Anders; Boeriis, Morten (Routledge, 2018)
"As a founder and leading figure in multimodality and social semiotics, Theo van Leuween has made significant contributions to a variety of research fields, including discourse analysis, sociolinguistics, communication and media studies, education, and design. In celebration of his illustrious research career, this volume brings together a group of leading and emerging scholars in these fields to review, explore and advance two central research agendas set out by van Leeuwen: the categorisation of the meaning potential of various semiotic resources and the examination of their uses in different forms of communication, and the critical analysis of the interaction between semiotic forms, norms and technology in discursive practices. Through 11 cutting-edge research papers and an experimental visual essay, the book investigates a broad range of semiotic resources including touch, sound, image, texture, and discursive practices such as community currency, fitness regime, film scoring, and commodity upcycling. The book showcases how social semiotics and multimodality can provide insights into the burning issues of the day, such as global neoliberalism, terrorism, consumerism, and immigration."- Resumé vydavatel
Keywords: diskurzivní analýza; sociolingvistika; sémiotika; discourse analysis; sociolinguistics; semiotics; multimodální komunikace; elektronické knihy; studie; electronic books; studies